What developments are needed to achieve less-invasive urodynamics? ICI-RS 2019 - TARCAN, TUFAN (WILEY, 2020)
Aims To assess the state of technologies for urodynamics that are less invasive than standard cystometry and pressure-flow studies and to suggest areas needing research to improve this. Methods A summary of a Think Tank debate held at the 2019 meeting of the International Consultation on Incontinence Research Society is provided, with subsequent analysis by the authors. Less-invasive techniques were summarized, classified by method, and possible developments considered. Discussions and recommendations were summarized by the co-chairs and edited into the form of this paper by all authors. Results There is a full spectrum of technologies available for less-invasive assessment, ranging from simple uroflowmetry through imaging techniques to emerging complex technologies. Less-invasive diagnostics will not necessarily need to replace diagnosis by, or even provide the same level of diagnostic accuracy as, invasive urodynamics. Rather than aiming for a technique that is merely less invasive, the priority is to develop methods that are either as accurate as current invasive methods, or spare patients from the necessity of invasive methods by improving early triaging. Conclusions Technologies offering less-invasive urodynamic measurement of specific elements of function can be potentially beneficial. Less-invasive techniques may sometimes be useful as an adjunct to invasive urodynamics. The potential for current less-invasive tests to completely replace invasive urodynamic testing is considered, however, to be low. Less-invasive techniques must, therefore, be tested as screening/triaging tools, with the aim to spare some patients from invasive urodynamics early in the treatment pathway.
Keywords: new technologies; noninvasive; BLADDER OUTLET OBSTRUCTION; DETRUSOR; UROFLOWMETRY; DIAGNOSIS; SYMPTOMS; PATIENT; WOMEN; MEN